Pembuatan Program Kompresi dengan Metode Pengkodean Huffman - Tamatjita, Elizabeth Nurmiyati; Jap, Wie Tjhe (Computatio : Journal of Computer Science and Information Systems, 2023)
A well known compression method is Huffman Coding. This method replace data with a code called Huffman code. The code be created from binary tree traversal. The code is saved in a file as header file. Compressed data is saved after header file. This research discuss how to save Huffman Code and compressed data into a file and how to decompress it.